O corpo, a educação física e o curso normal regional: memórias do Instituto Estadual de Educação Ponche Verde - Piratini/RS - Passos, Angela Alves dos (2010)
The principal objetive this study was to build part of memories from Instituto Estadual de Educação Ponche Verde, situated in municipality of Piratini RS. The search priorited the investigation the course about formation of teachers, in special the Normal Regional (1954 1971) and the Physical Education post in practice in this education space. The search was developed having with theoretical-methodology reference the conception of history of Michael Foucault, the studies of memory and the beginning methodologies of Oral History. This way, was utilized written fontain (institutions documents, registers, reports, decrees, laws, newspaper reports of city), old photographs and oral declaration of old members of school. The conclusion of search marked how the course about formations de teachers Normal Regional Ponche Verde was a center to irradiate of education and of culture, in city and in a region, that performed by beginning of moral, well-breds and of adhesion to public interests and welfare and, with assistance of Physical Education (gymnastics method) helped in a constitution of a disciplined body and cordial for the discourse and the socials norms effective in different epochs